Nanocomposite electrodes for high current density over 3 A cm−2 in solid oxide electrolysis cells - Hiroyuki Shimada (Nature Portfolio, 2019)
High-temperature solid oxide electrolysis cells are a promising technology for energy conversion, but higher current density is needed to increase efficiency. Here the authors design nanocomposite electrodes to improve electronic and ionic conductivity to achieve a high current density.